Pengembangan Video Animasi Suhu dan Kalor Menggunakan Aplikasi Animaker Berbasis STEM - Khairul Rizal Pratama; Artha Nesa Chandra; Venny Haris; Novia Lizelwati (Edusainstika: Jurnal Pembelajaran MIPA, 2022)
After the Covid-19 pandemic, the learning system changed. Learning must use appropriate and IT-based media. The limitations of the learning media used, the view that learning physics is difficult coupled with the learning methods used by the teacher tends to make students lazy. As a result, this has an impact on the value of students. The solution is that researchers develop physics learning videos using STEM-based Animaker applications. This study aims to develop physics learning videos to support physics learning on temperature and heat material. The type of research used is research and development which refers to the 4D development model (Define, Develop, and Disseminate). However, the research was only carried out until the development stage due to time and cost limitations. The instrument data used is a product validation sheet. Research data was obtained from two lecturers and one teacher. The results of research and discussion that physics learning videos using STEM-based Animaker applications on temperature and heat material are declared valid with the percentage of each aspect, content quality aspect 80.20%, instructional aspect 86.45%, technical aspect 64.28% so that the total number of aspects obtained results with a percentage of 77.17% which is categorized as valid.